2023
DOI: 10.3390/cancers15041041
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Hemojuvelin and Ferritin: Potential Prognostic Markers in Pediatric Hematopoietic Cell Transplantation

Abstract: Objective: Iron overload (IO) is a common and life-threatening complication resulting from the therapy of AL and HCT patients. This study aimed to evaluate the prognostic value of 12 serum biomarkers of iron metabolism in pediatric patients treated for AL or undergoing HCT. Patients: Overall, 50 patients with AL after intensive treatment and 32 patients after HCT were prospectively included in the study. AL patients at diagnosis and healthy controls served as reference groups. Methods: The impact of the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Several categories of iron metabolism markers have already been measured for prognostic purposes in children with febrile urinary tract infection and in children after intensive chemotherapy for acute leukemias or undergoing hematopoietic cell transplantation. So, parameters determining functional and storage iron pool (iron, total iron-binding capacity, transferrin, ferritin, ferritin heavy and light chain), proteins contributing to the absorption of iron and its release from tissues stores (hepcidin, soluble ferroportin-1 and soluble hemojuvelin) and proteins determining the erythropoietic activity of the bone marrow (erythropoietin, erythroferrone, and soluble transferrin receptor) [61,62] could be considered for future research also in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Several categories of iron metabolism markers have already been measured for prognostic purposes in children with febrile urinary tract infection and in children after intensive chemotherapy for acute leukemias or undergoing hematopoietic cell transplantation. So, parameters determining functional and storage iron pool (iron, total iron-binding capacity, transferrin, ferritin, ferritin heavy and light chain), proteins contributing to the absorption of iron and its release from tissues stores (hepcidin, soluble ferroportin-1 and soluble hemojuvelin) and proteins determining the erythropoietic activity of the bone marrow (erythropoietin, erythroferrone, and soluble transferrin receptor) [61,62] could be considered for future research also in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations include the use of cross-sectional data, which cannot establish a causal relationship between IDA and the associated risk factors in CU5 and WRA. There have been suggestions that other biomarkers, such as hepcidin [51] and hemojuvelin [52], might improve the assessment of iron deficiency and responsive anemia, although this has not been borne out of trials using a targeted approach to supplementation with hepcidin [53]. Other studies have also suggested doing away with altitude adjustment [54] for anemia, but consensus in this aspect is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory markers of iron metabolism in serum can be categorized as (1) parameters determining storage and functional iron pool (ferritin, serum iron, total iron-binding capacity, transferrin, and transferrin saturation); (2) proteins regulating iron absorption and release from tissues stores (hepcidin, soluble ferroportin-1, and soluble hemojuvelin); and (3) proteins indicating erythropoietic activity (erythropoietin (EPO), soluble transferrin receptor (sTfR), and erythroferrone [69,70]). Some of the more extensively studied perinatal iron indices are reviewed below.…”
Section: Serum Iron Panelmentioning
confidence: 99%